The subversions of deconstruction and the resistances of Aufhebung: Hegel tra passato e futuro in Jacques Derrida e Catherine Malabou - Baptist, Gabriella (B@belonline, 2022)
Jacques Derrida’s Glas (1974) and Catherine Malabou’s L’Avenir de Hegel (1996) rework the question of Hegel’s legacy in contemporary thought by drawing attention to the speculative and dialectical force of the Aufhebung and its perspectives. In an original way they re-propose the problem of the relation of thinking to time, especially in the reference to the famous pages on absolute knowledge at the end of the Phenomenology of Spirit.